Manajemen Sumber Daya Manusia dalam meningkatkan mutu Pendidikan guru SMK TIRTA KENCANA : - Chandra Sagul Haratua; Andre Bara Windana; Tenny Mandasari (Lancar Media Komunikasi, 2023)
Human resource management is a form of effort to improve quality in the development of an educational institution. Improving the quality of human resources requires a mechanism that is able to regulate and optimize the various components of human resources in schools, including educators and education staff. The purpose of this study is to find out the natural background of SMK, the implementation of human resource management in improving the quality of education based on planning, organizing, directing, controlling, procuring, developing, compensating, integrating, maintaining, discipline, dismissal, quality of education, obstacles faced and effort. Research using descriptive qualitative method. Human resource management from the aspect; planning based on the scale of needs, organizing involving organizational administrators, directingjob description predetermined, control basedQuality Assurance (QA), Increasing teaching staff through training. The quality of education uses process standards to achieve graduate competency standards. Keywords: Management, Resources, Resources, People, Quality, Education